Grooved-structure design for improved component damping ability. (July 2018) - Zhang, Q.; Mo, J.L.; Lu, X.D.; Zhao, J.; Wang, D.W.; Zhou, Z.R.
Abstract: To investigate the influence of the different structures of elastic damping components on vibration performance and tribological characteristics, different-angled grooved structures were designed and manufactured on the damping components and damping ability tests were carried out on the developed experimental setup. Results showed that the system with grooved-structure damping components exhibited a lower vibration amplitude and better contact conditions for a pad surface than the system without a damping component. To provide a possible explanation of why the improvement effect of different damping components on damping abilities exhibited discrepancy, a hammer impact test was carried out and the contact pressure distribution on a pad surface and the deformations of different grooved damping components were simulated using the finite element method. Graphical abstract: Image 1 Highlights: Grooved-structure damping components for improved damping ability are designed. Grooved-structure damping components show a decreased storage modulus. Grooved components effectively absorb the energy of the friction-induced vibration. Larger deformation of components helps adjusting the contact pressure distribution.